2015
DOI: 10.1371/journal.pone.0133519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adaptation Rate and Noise Suppression on the Intelligibility of Compressed-Envelope Based Speech

Abstract: Temporal envelope is the primary acoustic cue used in most cochlear implant (CI) speech processors to elicit speech perception for patients fitted with CI devices. Envelope compression narrows down envelope dynamic range and accordingly degrades speech understanding abilities of CI users, especially under challenging listening conditions (e.g., in noise). A new adaptive envelope compression (AEC) strategy was proposed recently, which in contrast to the traditional static envelope compression, is effective at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Using vocoder simulations for the NH listeners under various background noise, speech maskers or numbers of electrodes were found in many previous studies as the proven strategy to understand and further provide basic information on the speech processing in CI users [55], [56], [57], [58], [59], [25], [60]. However, vocoder simulations were not used for estimating the precise level of performance for each single CI user.…”
Section: Methodsmentioning
confidence: 99%
“…Using vocoder simulations for the NH listeners under various background noise, speech maskers or numbers of electrodes were found in many previous studies as the proven strategy to understand and further provide basic information on the speech processing in CI users [55], [56], [57], [58], [59], [25], [60]. However, vocoder simulations were not used for estimating the precise level of performance for each single CI user.…”
Section: Methodsmentioning
confidence: 99%
“…Amplitude Envelope and Spectrogram Analyses on Vocoded Speech In addition to waveform and spectrogram plots, amplitude envelope plots are another useful tool for analyzing time-varying signals [97,98]. Previous studies [85,97,98] have reported a positive correlation between the modulation depth of the amplitude envelope and speech intelligibility. It has also been shown that the middle frequency band is more important for speech intelligibility than the low-and high-frequency bands.…”
Section: )mentioning
confidence: 99%
“…In addition, vocoder has a profound impact on CI research. Using vocoder, speech signals are processed to simulate the sound heard by CI users, and the simulations are presented to NH participants for listening tests for various purposes, such as predicting the general pattern of speech recognition performance of CI users [14,[63][64][65]. Research using vocoder simulations may solve patient-recruitment issues as well as avoid patient-specific confounding factors, such as neural surviving patterns [64,66].…”
Section: Vocoded Speechmentioning
confidence: 99%
“…The participants were instructed to repeat verbally what they had heard. We evaluated the speech intelligibility under each test condition using the word correct rate (WCR) [38][39][40][41][42] calculated as the ratio between the number of correctly identified words and the total number of words. To further prevent participant fatigue, tests were paused for 5 minutes every 30 minutes.…”
Section: Training and Evaluation Proceduresmentioning
confidence: 99%